Studi Tentang Kondisi Hutan dan Dampaknya di Kecamatan Weda Utara Kabupaten Halmahera Tengah - Takdir Can; Ilham Majid; Abdulrasyid Tolangara (FKIP Universitas Khairun, 2025)
This study aims to determine the current condition of the forest in the Weda Utara sub-district, to determine mining activities that have an impact on forest conditions in the Weda Utara sub-district, to determine the impact of mining on the conversion of forest land in the Weda Utara sub-district. The research method used to research the natural object conditions, where the researcher is the key instrument, data collection techniques are carried out by triangulation (combination), data analysis is inductive, and qualitative research results emphasize meaning more than generalization. Data collection techniques used in this study are by using Observation, Literature Study, Interview, and Documentation. Data analysis techniques in the study using Data Reduction, Data Display, and Conclusion Drawing (Verification). The results of the study showed that: 1) The condition of the forest in Weda Utara District consisting of 5 villages (Gemaf, Sagea, Kiya, Fritu, and Waleh Villages) was very different between before and after mining activities, namely before mining activities. 2) Mining activities have an impact on forest conditions and the environment as well as Public Health in the form of loss of community livelihoods and a decrease in wildlife populations. 3) The impact of forest land conversion in North Weda District can be in the form of loss of forest cover and risk of flooding, water pollution and clean water crisis, erosion and decline in soil quality, loss of livelihoods, and respiratory diseases due to pollution.